RUANG LINGKUP MAQASID DALAM TAFSIR AL-TAHRIR WA’L-TANWIR - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
‘Allal al-Fasi. (1993). Maqasid al-Shari‘a al-Islamiyya wa Makarimuha, ed. ke-5. Beirut: Dar al-Gharb al-Islami. ‘Izz al-Din, Said Kashnit al-Jaza’iri. (2011). Ummahat Maqasid al-Qur’an: Turuq Ma‘rifatiha wa Maqasiduha. Amman: Dar al-Majdalawi li al-Nashr wa al-Tawzi‘. Afrizal Nur, Mukhlis Lubis, Hamdi Ishak (2017). ‘Sumbangan Tafsir al-Tahrir wa al-Tanwir Ibn ‘Ashur dan Relasinya dengan Tafsir al-Mishbah M. Quraysh Shihab’, Jurnal al-Turath, 2 (2), 67–79. Aksin, W. (2021). Shofiyullah Muzammil, ‘Maqasidi Tafsir: Uncovering and Presenting Maqasid Ilahi-Qur’ani into Contemporary Context’, Al-Jami‘ah: Journal of Islamic Studies, 59.2. Al-Alwani, Taha Jabir Fayyad. (1993). Ijtihad. London & Herndon, VA: IIIT. Al-Raysuni, Ahmad. (1991). Nazariyyat al-Maqasid ‘inda al-Imam al-Shatibi. Rabat: Matba‘ah al-Najah al-Jadidah. Al-Raysuni, Ahmad. (2013). Imam al-Shatibi’s Theory of the Higher Objectives and Intents of Islamic Law. Nancy Roberts (terj.). London & Washington: IIIT. Al-Shatibi, Abu Ishaq Ibrahim. (2006). Al-Muwafaqat fi Usul al-Shari‘ah. ‘Abdullah Darraz (pytg.). Mesir: Dar al-Hadith. Atfal, K. (2023). “Mengenal Tafsir at-Tahrir wa at-Tanwir karya Tahir ibn Ashur”. tafsiralquran.id https://tafsiralquran.id/mengenal-tafsir-at-tahrir-wa-at-tanwir-karya-%E1%B9%ADahir-ibn-ashur/ diakses 24 November 2023. Auda, J. (2023). Maqasid Syariah Sebagai Falsafah Perundangan Islam: Pendekatan Sistem. Tr. Muhammad Razak Idris. Kuala Lumpur: Penerbit Universiti Malaya. Basheer M. Nafi, ‘Tahir ibn ‘Ashur. (2025). The Career and Thought of a Modern Reformist ‘alim, with Special Reference to His Work of tafsir’, Journal of Qur’anic Studies, 7.1. Brown, Jonathan A.C. (2014). Misquoting Muhammad (s): The Challenge and Choices of Interpreting the Prophet’s Legacy. UK: Oneworld Publications. el-Mesawi, Mohamed el-Tahir. (2009). “Human Nature and the Universality of the Shari‘ah: Fitrah and Maqasid al-Shari‘ah in the Works of Shah Wali Allah and Ibn ‘Ashur”. Al-Shajarah 24 (2), 167-205. el-Mesawi, Mohamed el-Tahir. (2018). Maqasid al-Shari‘ah: Explorations and Implications. Petaling Jaya: Islamic Book Trust. el-Mesawi, Mohamed el-Tahir. (2020). “Maqāsid al-Sharī‘ah: Meaning, Scope and Ramifications”. Al-Shajarah 25.2, 263-295. Fadzil, S. (2022). Maqasid al-Shari‘ah dalam Ranah Demokrasi. Shah Alam: UNISEL Press. Firdaus, M.A. (2020). “Maqasid al-Qur’an sebagai Paradigma Pendidikan Islam (Konstruksi Pemikiran Islam Ibn ‘Ashur)”. PhD. diss., UIN Sunan Ampel Surabaya. Hamid, M.B.A. (2021). Citra Maqasid al-Shari‘ah: Dari Kelahiran hingga Kebangkitan. Kuala Lumpur: ABIM Press. Hasanah, I.N. (2022). “Mengenal Kitab at-Tahrir wat Tanwir, Ensiklopedi Tafsir karya Bin Asyur”, Nu online. https://islam.nu.or.id/tafsir/mengenal-kitab-at-tahrir-wat-tanwir-ensiklopedi-tafsir-karya-bin-asyur-14gcv, diakses 14 Maret 2022. Ibn Ashur, Mohammad al-Tahir. (2006). Ibn Ashur – Treatise on Maqasid al-Shariah. Tr. Mohamed el-Tahir el-Mesawi. London & Washington: IIIT. Ibn Ashur, Mohammad Tahir. (1994). Tafsir al-Tahrir wa al-Tanwir. Vol. 1. Tunisia: al-Dar al-Tunisiyyah li al-Nashr. Ibn Ashur, Mohammad Tahir. (2001). Maqasid al-Syari‘ah al-Islamiyyah, Muhammad Tahir al-Misawi (pytg.). Amman, Jordan: Dar al-Nafa’is. Ibn Ashur, Mohammad Tahir. (2006). Alaysa al-Subh bi Qarib, al-Ta‘lim al-Araby al-Islamy Dirasah Tarikhiyyah wa Ara’ Islahiyyah. Tunisia: Dar al-Salam li al-Tiba‘ah wa al-Tawzi‘ wa al-Nashr wa al-Tarjamah. Ibn Ashur, Mohammad Tahir. (tt). Usul al-Nizam al-Ijtima‘i fi al-Islam. Tunisia: al-Shirkah al-Tunisiyyah li al-Tawzi. Jani Arni. (2011). “Tafsir al-Tahrir wa al-Tanwir Karya Muhammad al-Tahir ibn Asyur”, Jurnal Ushuluddin XVII, no. 1, 80-97. Lit Supriatin, Dudi Ismail, Neneng Nia Kurniasih. (2025). ‘Tanazzul sebagai Taklif: Tafsir Maqasidi atas Peran Adam sebagai Khalifah’, Al-Ibanah Jurnal Keislaman, Kemasyarakatan dan Pendidikan, 10.2, 149–156. Mahmassani, S. (1961). Falsafat al-Tashri‘ fi al-Islam: Muqaddima fi Dirasat al-Shari‘a al-Islamiyya ‘ala Daw’ Madhahibuha al-Mukhtalifa wa Daw’ al-Qawanin al-Haditha. Beirut: Dar al-‘Ilm lil-Malayin. Mohamad, K.A. (2021). “Kehebatan Kaedah Tafsir al-Maqasidiy Ibn Asyur”. utusanmalaysia https://www.utusan.com.my/gaya/agama/2021/01/kehebatan-kaedah-tafsir-al-madasidiy-ibn-asyur/ diakses 5 Januari 2021. Mokhtar, R. (2019). Tadabbur Wahyu: Ringkasan dan Ulasan Kitab al-Tahrir wa al-Tanwir Karya Ibn ‘Asyur. Siddiq Fadzil (pengantar). Nilai: Ilham Books. Muhamad Anwar Aditya, Rofiqoh Nurul Ashfiya, M Yusril Mubarak. (2025). ‘The Ethics of Interpretation in Maqasidi Exegesis: An Exploration of the Framework in Ibn Asyur’s Muqaddimah’, Zad al-Mufassirin, 7.1, 100–122. Syamsuri. (2025). ‘Kredibilitas Ibnu Mas‘ud dalam Tafsir al-Qur’an dan Kontribusinya terhadap Pengembangan Tafsir Maqasidi’, Pegon: The International Journal of Islam Nusantara Civilization, 14.1, 163–201. Syaza Shukri, Meor Alif Meor Azalan. (2023). “The Application of Maqasid al-Shariah in Multicultural Malaysia: Developing Strong Institutions for Interethnic unity”, Contemporary Islam 17, 433-450. Yudha, M.A. (2023). ‘Uncovering the Human and Divine Aspect of Ridha in the Qur’an through the Lens of Tafsir Tahrir wa Tanwir’, Jurnal Studi Ilmu-Ilmu al-Qur’an dan Hadis, 24.1, 119–136. Zulkifli Mohamad al-Bakri (kata aluan). (2020). Minda Maqasid. Putrajaya: Jabatan Kemajuan Islam Malaysia. Zulkifli Mohamad al-Bakri. (2014). Maqasid Syariah Satu Pengenalan Umum. Nilai: Pustaka Cahaya Kasturi.